Microorganism-mediated algal biomass processing for clean products manufacturing: Current status, challenges and future outlook. (1st March 2022) - Abd El-Malek, Fady; Rofeal, Marian; Zabed, Hossain M.; Nizami, Abdul-Sattar; Rehan, Mohammad; Qi, Xianghui
Highlights: Algal biomass (AB) have received significant research attention in 3G biorefinery. Microbial conversion of AB can produce diverse industrially important products. Microbial AB processing can produce biopolymers, peptides, bioacids, and biofuels. Future advancement of green technology utilizing algal-microbial systems. Abstract: The global demand for clean products obtained from biobased resources has increased significantly with the rapid growth of the world's population. In this context, microbially-produced compounds are highly attractive for their safety, reliability, being environment friendly and sustainability. Nevertheless, the cost of the carbon sources required for such approaches accounts for greater than 60% of the total expenses, which further limits the scaling up of industries. In recent years, algae have been used in numerous industrial areas because of their rapid growth rate, easy cultivation, ubiquity and survival in harsh conditions. Over the past decade, notable advances have been observed in the extraction of high-value compounds from algae biomass (ABs). However, few studies have investigated ABs as green substrates for microbial conversion into value-added products. This review presents the potential of ABs as the substrates for microbial growth to produce industrially-important products, which sheds light on the importance of the symbiotic relationship between ABs and microbial species. Moreover, the successful algal-bacterial gene transformation paves the way for accommodating green technology advancements. With the escalated need for natural pigments, biosurfactants, natural plastics and biofuels, ABs have been new resources for microbial biosynthesis of these value-added products, resolving the problem of high carbon consumption. In this review, the fermentative routes, process conditions, and accessibility of sugars are discussed, together with the related metabolic pathways and involved genes. To conclude, the full potential of ABs needs to be explored to support microbial green factories, producing novel bioactive compounds to meet global needs.